2001
DOI: 10.1258/0004563011901127
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin measured on a blood gas analyser: a suitable alternative for near-patient assessment of neonatal jaundice?

Abstract: The reliability of a recently released total bilirubin assay for a blood gas analyser was assessed in two Australian hospital laboratories. The instrument computes total bilirubin concentration from multi-wavelength absorbance measurements of undiluted whole blood or plasma. Performance of the Radiometer ABL 735 blood gas analyser bilirubin method (software version 3.6) was compared with a proven Roche diazo method for Hitachi analysers, calibrated using primary standards prepared from NIST SRM 916a bilirubin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The results of Passing-Bablok regression analysis and Bland-Altman deviation chart analysis showed that the consistency of the two methods was poor, especially in the >300 μmol/L Group. The cause of deviation may have been the interference of neonatal hemoglobin (11), the calculation of plasma equivalent on the blood gas analyzer (7,12), the increase of bound bilirubin or delta bilirubin in the sample, and different albumin levels (13,14). There may also have been C D E methodological differences between blood gas analyzers and chemical analyzers (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Passing-Bablok regression analysis and Bland-Altman deviation chart analysis showed that the consistency of the two methods was poor, especially in the >300 μmol/L Group. The cause of deviation may have been the interference of neonatal hemoglobin (11), the calculation of plasma equivalent on the blood gas analyzer (7,12), the increase of bound bilirubin or delta bilirubin in the sample, and different albumin levels (13,14). There may also have been C D E methodological differences between blood gas analyzers and chemical analyzers (11).…”
Section: Discussionmentioning
confidence: 99%
“…The cause of deviation may have been the interference of neonatal hemoglobin (11), the calculation of plasma equivalent on the blood gas analyzer (7,12), the increase of bound bilirubin or delta bilirubin in the sample, and different albumin levels (13,14). There may also have been C D E methodological differences between blood gas analyzers and chemical analyzers (11). Meanwhile, it should be noted that the biochemical analyzer (enzymatic method) as the gold standard also needs to be standardized (15).…”
Section: Discussionmentioning
confidence: 99%
“…Capillary samples are measured using spectrophotometry with multiple wavelength readings and algorithms to correct for haemoglobin, fetal haemoglobin and lipaemia. Comparisons with wet 46,47 and dry slide 48 Diazo laboratory methods for neonates have shown an insignificant bias over a wide range of bilirubin concentrations, albeit with a wide scatter.…”
Section: First-line Assessment Of Jaundicementioning
confidence: 99%
“…8,9 However, most existing methods for optical analysis of turbid media are not able to extract a , s , and g simultaneously and many methods also focus on either the absorption or the scattering properties, i.e., the scattering effects are treated as interference during absorption measurements 9,10 or vice versa. 11,12 Yet other methods rely on removal of the scattering components prior to absorption measurements, e.g., some types of clinical blood analysis 13,14 where the blood cells are hemolyzed (the cell walls are crushed) and subsequently removed from the sample either by means of sedimentation or centrifugation.…”
Section: Introductionmentioning
confidence: 99%